PENGARUH PEMIKIRAN ULAMA TIMUR TENGAH TERHADAP GERAKAN ISLAM POLITIK DI YOGYAKARTA DAN SURAKARTA - Istadiyantha, Istadiyantha (Jurnal CMES, 2013)
In this research, the term Political Islamic Movement is used as the equivalencyof Islamic Fundamentalism terminology. In the referral taking as the references for thesedissertation and article, the writer still use the origin terminologies written by authors ofbibliography, in order to fit the quotations with the original writersâ€™ thought. Thus, theterms Political Islamic Movement, Islamic Fundamentalist, Islamic Militant, and IslamicRadical are being used together in this dissertation, only Political Islamic Movementdominantly used, and the term chosen by the writer due to this term is agreed by manyIndonesian expertise as the typical appropriate term come from Bahasa Indonesia, toreplace Islamic fundamentalism term. Â Political Islamic Movement in Yogyakarta and Surakarta had been observedgetting the impact of Salafiyah Movement or Wahabiyah, and also Al-Ikhwan. Formerly,Al-Ikhwan was not a new movement, due to Al-Ikhwan movement was the completionresult from the former movements which appeared in Mid East such as Wahabiyah,Sanusiyah, and Mahdiyah. So is Wahabiyah Movement, it did not suddenly appear as newthought, and yet it was an effort to strengthen to the former ideology, which is Salafiyah,this ideology was formerly proposed by Al Imam Ahmad Bin Hanbal.